Compromising long-term sustainability for short-term profit maximization: Unethical business practice - Mishelle Doorasamy; Kiran Baldavaloo (Foundations of Management, 2016)
The current environmental challenges caused by the dependence on nonrenewable energy, increased waste disposal, the toxic emissions created by operational activities, and also the scarce supply of water are so complex and important that it requires immediate attention. Strict environmental legislation, market pressures, and urgent need for sustainability have given businesses no option but to ensure that they do all that is possible to ensure that their business operations are sustainable. This paper addresses the underlying factors that determine the extent to which organizations adopt sustainable business practices and cleaner production techniques and technologies. It had been concluded that ethics is linked to sustainable business practices, because the objectives of both these concepts are to think about doing what's right for others and the world, including the environment. According to the organizational corporate compliance regulations, a company's commitment to ethical business and sustainable business practices should be detailed in their policy handbook and communicated to all employees within the company (Sustainability Report 2013/2014).
Keywords: 650; sustainable development; business ethics; eco-efficiency; ISO14001; environmental performance; triple bottom line